(untitled) (Journal of Computational Mathematics, 2007)
In this paper we study the method of interpolation by radial basis functions and give some error estimates in Sobolev space H^k(Ω) (k ≥ 1). With a special kind of radial basis function, we construct a basis in H^k(Ω) and derive a meshless method for solving elliptic partial differential equations. We also propose a method for computing the global data density.